(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present paperis primarily an attempt to understand the patterns ofreligious worship in some villages in the north-west Delhi. It discusses themacro-level perspective of the issues with reference to the current beliefs andpractices that are a significant part of the sacred lives of the peasantcommunities. There are several ways to study religion among which texts oftenhave been given a fundamental place. Textual prescriptions and proscriptions,however, can have a marginal role in the world of folk worship. Therefore, inthis case, diverse forms of customs and traditions of the various communitieswhich coexist and which can be observed are studied from the perspective ofarchaeology. The aim of the work is to analyze ‘rural religion’ with specialreference to archaeological evidence from select villages in order tounderstand the interconnected aspects of the sacred geography of the area as awhole. The reason to choose the area to study these aspects is that thevillages are in close proximity to the urban parts of the city where ‘Brahmanicreligious traditions’ hold prominence, however, it will be argued that thoughthe religious lives of the villages are not untouched by city culture, in thesacred universe of the peasant communities, local deities are moresignificance. Physiographically, the area situated to the north of thecapital city is composed of two contrasting zones- the old alluvium, popularlyknown as ‘Bangar’ and the newalluvium or ‘Khadar’. The low Khadar lands lie near the Jumna River and the higher Bangar lands removed from theinfluence of the floods of the Jumna. The soil of the Bangar is composed of loam, clay and aeolian sandy soils. Themajority of land of these villages belongs to the Jats, who are the Zamindars or the landowning class.The agricultural population of Delhi consists chiefly of Jats, who own nearlythe half the area of the district.